Authority of National Police Commission to Enhance The Professionalism of National Police of Indonesia - Marjon, Dahlil (International Journal of Social and Local Economic Governance, 2015)
National Police Commission of Indonesia is regarded by many as an external oversight committee Indonesian National Police, although in reality this assumption wrong. National Police Commission is not an external police oversight commission. It is said not by the external oversight committee is not equipped with the authority to examine and investigate the perpetrators of violations of codes of conduct and abuse of authority other duties.The purpose of the research in this paper is first, to examine and analyze how the existence of the National Police Commission in terms of construction law as an external watchdog Indonesian National Police, second, to examine and analyze why the authority of the National Police Commission did not reflect the external oversight bodies Indonesian National Police, the third, to examine and analyze how forms of authority and duties that should be owned by the National Police Commission as an external watchdog Indonesian National Police.Contributions expected from this research are to enrich the knowledge and understanding to empower an organization, particularly the National Police Commission, related to the functions, duties and authority of the National Police Commission, especially in terms of authority to do inspections and investigations against police officers and the perpetrators of violations of the code of conduct abuse of authority other duties.Conclusion of the study explained that the absence of authority to inspect and conduct an investigation of police officers and the perpetrators of violations of ethics code violations authority other duties affect the effectiveness performance of duties as a watchdog function. National Police Commission is not able to check and investigate the police officers concerned.Keywords: professionalism, oversightor, external, authority, commission